Identifying unknown human bodies in Hungary since 1951 Part I. (Academic Journal of Internal Affairs, 2016)
The authors provide an overview of how unknown human bodies have been identified in Hungary in the past 65 years.
Keywords: identification; unknown human body; Hungary